2014
DOI: 10.1080/14680629.2014.927951
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-induced strength degradation of aggregate–asphalt mastic bonds

Abstract: A common manifestation of moisture-induced damage in asphalt mixtures is the loss of adhesion at the aggregate-asphalt mastic interface and/or cohesion within the bulk mastic. This paper investigates the effects of moisture on the aggregate-mastic interfacial adhesive strength as well as the bulk mastic cohesive strength. Physical adsorption concepts were used to characterise the thermodynamic work of adhesion and debonding of the aggregate-mastic bonds using dynamic vapour sorption and contact angle measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 18 publications
6
33
0
1
Order By: Relevance
“…This is due to the improvement in the free cohesion energy of asphalt binder and also the free adhesion energy of asphalt binder-aggregate. 4. Adding PP significantly increases resistance against moisture damage and increases the amount of the indirect tensile rate in the samples that are modified with this material in comparison with the control mixtures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the improvement in the free cohesion energy of asphalt binder and also the free adhesion energy of asphalt binder-aggregate. 4. Adding PP significantly increases resistance against moisture damage and increases the amount of the indirect tensile rate in the samples that are modified with this material in comparison with the control mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, moisture damage occurs because moisture has less viscosity and surface tension in comparison with the asphalt binder [4]. This leads the aggregates to tend to be adjacent water rather than the asphalt binder which makes the stripping to be happened.…”
Section: Introductionmentioning
confidence: 99%
“…losing the bond between aggregates and the binder [2]. Moisture damage is associated with stripping, excessive permanent deformation and cracking [3,4]. Therefore, predicting the hydraulic conductivity and understanding the factors influencing it will help to establish a balance between deterioration and drainage performance.…”
Section: Introductionmentioning
confidence: 99%
“…Further, none of these tests describe a mechanism behind bonding and debonding of aggregates-asphalt system [1,2]. Recently, researchers reported that surface free energy (SFE) of asphalt binder and aggregates can be a promising parameter in identifying a moisture resistant mix [3][4][5][6][7][8]. The SFE of aggregate and asphalt binder is used to estimate dry and wet adhesion energy and compatibility ratio (CR) to evaluate moisture susceptibility of asphalt mixes.…”
Section: Introductionmentioning
confidence: 99%